Green supply chain management for the SME automotive suppliers. (1st January 2013) - Lin, Liang-Hung; Lan, Jian-Feng
With the rise of environmental awareness, regulations in various countries become stricter, which consequently results in environmental pressures. In this study, we analyse the relationship of green supply chain management (GSCM) and institutional pressures with environmental performance of firms in the auto component industry, as well as the relationship between small and medium enterprises (SMEs) and corporate social responsibility (CSR). Moreover, we study 224 firms in Taiwan by means of questionnaires and the results show that investment recovery and eco-design in GSCM as well as normative pressures in institutional pressures positively relate to a firm's environmental performance. Moreover, SMEs tend to do more external GSCM practice and internal environmental management.